Heritage tourism destinations : preservation, communication and development - Alvarez, Maria D. (Maria Dolores); Go, Frank M.; Yüksel, Atila (CAB International, 2016)
This book on heritage tourism utilizes a three-part structure. Part I (chapters 1-3) deals with the conservation and revitalization of heritage destinations, as well as the role local communities have in supporting an attraction. Part II (chapters 4-6) discusses the development of heritage tourism destinations as tourism products, and the communication process involving the endogenous characteristics and distinct traits pertaining to these places through non-conventional marketing pathways. Part III (chapters 7-11) introduces both theoretical perspectives on governance and stakeholder collaboration within the contexts of museums, archaeological sites and historical destinations with a focus on planning, governance models and institutional perspectives. This volume presents a range of international case studies that contribute to a better understanding of the topics outlined.